Analysis Of Transportation Infrastructure In Improving The Welfare Of The Bandar Sri Junjungan Dumai Ro-Ro Port Community - Salsa Bila Pitu Legiana; Ufira Isbah; Yelly Zamaya (Dinasti Publisher, 2025)
This research aims to identify the strengths and weaknesses of the existing transportation infrastructure, as well as the opportunities and threats faced in improving the welfare of the community around the port. This research was conducted with a descriptive analysis approach using SWOT to explore the experiences and views of the community around the Bandar Sri Junjungan Dumai Ro-ro Port. Based on the SWOT analysis, it shows that the port has strengths in the form of a strategic location that connects the Dumai region with various regions around the Malacca Strait. Opportunities that can be utilized for the development of transportation infrastructure at this port include increasing the capacity of the dock, developing logistics facilities and better road access, and utilizing digital technology to expedite port traffic management and monitoring systems. This port has considerable potential in supporting the welfare of the community around the port.